2020
DOI: 10.35366/92875
|View full text |Cite
|
Sign up to set email alerts
|

Reconversión hospitalaria ante la pandemia de COVID-19

Abstract: RESUMEN. La reconversión hospitalaria ha sido reconocida como uno de los puntos estratégicos de mayor relevancia a través de la historia de las pandemias. En el 2020, la OMS declaró la presencia de pandemia por COVID-19 el 11 de marzo. En consecuencia en el mundo y en nuestro país, se tomaron las medidas para llevar a cabo la reconversión hospitalaria de acuerdo con las posibilidades y capacidades propias de cada región. La velocidad de reacción requerida para la cristalización de la reconversión agrega un fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 8 publications
0
14
0
12
Order By: Relevance
“…While state-managed hospitals and private sector showed lower risks, in contrast the IMSS seems to be the one with the highest risk (Figure 3). Although it is worth mentioning that following the national hospital transformation plan [13], IMSS alone has transformed about 260 medical units to treat Covid-19 patients [14]. Additionaly it has the largest number of affiliations and they are liklely to have higher risk exposure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While state-managed hospitals and private sector showed lower risks, in contrast the IMSS seems to be the one with the highest risk (Figure 3). Although it is worth mentioning that following the national hospital transformation plan [13], IMSS alone has transformed about 260 medical units to treat Covid-19 patients [14]. Additionaly it has the largest number of affiliations and they are liklely to have higher risk exposure.…”
Section: Resultsmentioning
confidence: 99%
“…In this study we identified 6 different healthcare providers which were classified according to their sectors IMSS, ISSSTE, SEDENA/SEMAR/PEMEX, SSA, ESTATALES (healthcare provider within each state) these 5 are public care providers while the sixth sector is private hospitals. It is worth mentioning that following the national hospital transformation plan [13], IMSS alone has transformed about 260 medical units to treat COVID-19 patients [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear editor: During the Covid-19 pandemic, Mexico transformed hospitals that normally treated patients with chronic diseases into centers to treat Covid-19, 1 potentially displacing the care of patients with cancer. Mobile health (mHealth) could relieve health systems in low-and middle-income countries (LMIC) such as Mexico by offering an alternative to face-to-face contact at every stage of cancer care.…”
Section: Mhealth: Experiences and Opportunities For Cancer Research I...mentioning
confidence: 99%
“…Tomando en cuenta esos puntos, las zonas para la atención e ingreso de los pacientes sospechosos y confirmados de CO-VID-19, dentro de la organización se debe establecer una zona de triage para explorar y examinar pacientes, un laboratorio, una sala de observación y otra de reanimación, esto evitará que aumente la propagación y la contaminación del virus en otras áreas del hospital (Tabla 1) (1,11,14,(16)(17)(18)50) .…”
unclassified